Antimicrobial, modulatory and chemical analysis of the oil of Croton limae. (1st January 2017) - Leite, Tiago Rodrigues; Silva, Maria Arlene Pessoa da; Santos, Antônio Carlito Bezerra dos; Coutinho, Henrique Douglas Melo; Duarte, Antonia Eliene; Costa, José Galberto Martins da
Abstract: Context: Croton sp. are plants with a well-reported antimicrobial activity . Croton limae A.P. Gomes, M.F. Sales P.E. Berry (Euphorbiaceae), known as 'marmeleiro-prateado', is commonly used to manage abdominal pain in Brazil. Objective: This work evaluates the phytochemical composition, antimicrobial and modulatory activities of the essential oil of C. limae leaves (EOCL). Materials and methods: The minimum inhibitory concentration (MIC) and the modulation of the antibiotic activity were determined using a microdilution method. The concentration of EOCL ranged between 512 and 8  μg/mL. Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumonia, Candida tropicalis, C. krusei and C. albicans strains were used in the MIC and modulation assays. The antibiotics, amikacin, gentamicin and neomycin, and the antifungals, amphotericin B, benzoylmetronidazole and nystatin, were used in concentrations ranging between 2500 and 2.5  μg/mL. The phytochemical analysis of the EOCL was performed through gas chromatography coupled to a mass spectrometer (GC/MS). Results: Only Staphylococcus aureus was inhibited by a clinically relevant concentration of EOCL (MIC 512 μg/mL). Synergism between the EOCL and amikacin against S. aureus (9.76 μg/mL) and E. coli (39.062 μg/mL); neomycin against E. coli (2.44 μg/mL); and benzoylmetronidazole against C. krusei (256 μg/mL) were observed. The GC/MS analysis identified cedrol, eucalyptol and α-pinene as the main compounds of EOCL. Conclusion: EOCL inhibited the growth of S. aureus and potentiated the antibiotic and antifungal effects of drugs against all bacterial and Candida strains, respectively.